Clinical analysis of arthroscopic modified Mason-Allen suture in the repair of delaminated rotator cuff tears - Runqing Wu; Xiaoye Fang; Fangqi Xu; Shibing Xu; Longfeng Wang; Gangfeng Hu (BMC Musculoskeletal Disorders)
Abstract Purpose To observe the clinical efficacy and safety of arthroscopic single-row modified Mason-Allen(mMA) suture technique in repairing delaminated rotator cuff tears (RCTs). Methods According to the inclusion and exclusion criteria, a total of 65 selected cases were treated with mMA by a senior physician. Outpatient follow-up visits were conducted at 1.5 months, 3 months, 6 months, and longer after treatment. The postoperative shoulder range of motion (ROM), Constant Murely score (CS), and UCLA shoulder joint score were evaluated by the same examiner. After the follow-up, the data will be summarized and finally subjected to statistical analysis (Fig. 1). Results Collected 65 patients with delaminated RCTs repaired using arthroscopic modified Mason-Allen suture technique from May 2022 to June 2023. Three were lost to follow-up, leaving 62 patients who were included in the study analysis, including 21 males and 41 females; age ranged from 50 to 81 years old, with a median age of 65 years old; 34 cases in the left shoulder and 28 cases in the right shoulder; 30 cases with a history of trauma and 32 cases with no obvious history of trauma; According to the Cofield classification of RCTs, all were delaminated tears of the rotator cuff. We recorded changes in shoulder range of motion (ROM) and functional ratings for at least 6 months (6 months to 18 months, average 10 months) postoperatively. Shoulder anteflexion improved from 98.06 ± 11.28° to 172.26 ± 6.63° (P = 0.028), abduction improved from 69.68°±18.55° to 160.97 ± 9.53° (P = 0.006), internal rotation improved from 14.52°±10.35° to 45.81 ± 4.97° (P = 0.007), and external rotation improved from 22.42°±8.62°to 51.29 ± 6.14° (P = 0.027); CS preoperative 49.08 ± 4.91and at the last follow-up 97.89 ± 1.62 (P = 0.043); and UCLA shoulder score, preoperative 15.73 ± 2.60 and at the last follow-up 33.85 ± 0.15 (P = 0.044). 3 cases developed adhesive capsulitis symptoms due to inactive rehabilitation activities after the operation, and the symptoms disappeared after standard rehabilitation training (no secondary operation). All patients had no problems such as rotator cuff tearing and anchor removal. Conclusion The use of mMA suture technique to repair rotator cuff delamination tears can effectively relieve shoulder pain, improve shoulder function, and have fewer complications.